Impregnation of magnetic particles on oil palm shell activated carbon for removal of heavy metal ions from aqueous solution - Mohammad Zainol, Muzakkir (Penerbit UTM Press, 2015)
Oil palm shell activated carbon magnetic particle (CAC-MP) was prepared for adsorption of metal ions (Zn2+, Pb2+, Cu2+). Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), surface area and pore analysis (BET, BJH and t-plot method), field emission scanning electron microscopy (FESEM), vibrating sample magnetometer (VSM), and X-ray diffraction (XRD) were used to characterize CAC-MP. Its properties were compared with the parent activated carbon (CAC). The CACMP, with a high surface area (1007 m2/g), was used to study metal ions removal at different pH, adsorbent dosage, and contact time. The removal efficiency of metal ion increased with increasing pH, dosage, and time until equilibrium was reached. The optimum condition for maximum removal efficiency was at pH 6 and absorbent dosage of 0.5 g. Kinetic